Conceptualizing knowledge creation for batik aesthetics / Ariza Nordin - Nordin, Ariza (2011)
The research aims to conceptualize community-based information system model to enable batik aesthetics knowledge creation addressing cultural erosion phenomenon. The Malaysian batik community consists mainly of microenterprises is a viable selection of case because it represents a viable route in utilizing ICT as an enabler towards preservation of culture. Malaysia's participation in batik making traced back as early as 1900 dominantly located in the east coast region of Malaysian Peninsular. The Malaysian batik making business is experiencing culture erosion, deskilling and degradation due to a manifold of issues. The cultural erosion phenomenon is translated into traditional knowledge loss due to lack of knowledge transfer mechanism to enable batik makers to gain individual and community empowerment in preserving cultural identity. Within organizational model of product development, ICT has been acknowledged to have an enabling effect towards organizational knowledge creation cycle. However artisan community views technology as promoting imitations, a catalyst for cultural erosion problem through technology intoxication.